Quality and location choices under price regulation; Qualitäts- und Standortwahl bei Preisregulierung - Kurt R. Brekke; Robert Nuscheler; Odd Rune Straume (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
In a model of spatial competition, we analyse the equilibrium outcomes in markets where the product price is exogenous. Using an extended version of the Hotelling model, we assume that firms choose their locations and the quality of the product they supply. We derive the optimal price set by a welfarist regulator and find that this (second-best) price causes over-investment in quality and an insufficient degree of horizontal differentiation (compared with the first-best solution) if the cost of investing in product quality, or the transportation cost of consumers, is sufficiently high. By comparing the case of price competition, we also identify a hitherto unnoticed benefit of regulation, namely improved locational efficiency. – – In einem räumlichen Wettbewerbsmodell untersuchen wir die Gleichgewichte, die sich bei exogen gegebenem Preis einstellen. In einem erweiterten Hotelling Modell unterstellen wir, dass die Firmen den Standort (Produktdifferenzierung) und die Qualität ihres Produktes wählen. Wir ermitteln den, aus der Sicht eines sozialen Planers, optimalen Preis. Es zeigt sich, dass dieser (zweitbeste) Preis im Vergleich zum effizienten Ergebnis zu einer Überinvestition in Qualität und zu einer unzureichenden Produktdifferenzierung führt, wenn die Qualitätskosten der Firmen oder die Transportkosten der Konsumenten hinreichend groß sind. Ein Vergleich mit dem Marktergebnis bei Preiswettbewerb offenbart einen bisher unbeachteten positiven Effekt der Preisregulierung, den verbesserten Grad der Produktdifferenzierung.
Keywords: L13; L50; R30; R38; 330; Spatial competition; product quality; location; price regulation